PENGARUH PENGGUNAAN FINANCIAL TECHNOLOGY LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PENGELOLAAN KEUANGAN UMKM - NI NYOMAN JULI NURYANI; NI PUTU SONIA MELLYA UTAMI; MERTYANI SARI DEWI (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Small, medium, and micro businesses are among the most pursued businesses by some people because they have the potential to meet their living needs. Additionally, micro, small, and medium-sized businesses play a significant part increating jobs, helping to increase people's income through various economic activities ranging from trade to the creative industry. Behind the high interest in doing this business, there are still business actors who experience obstacles in managing their businesses where this is closely related to business financial management. The purpose of this study was to determine whether monetary technology, financial literacy and financial attitudes affect the financial management of Micro, Small and Medium Enterprises in Buleleng District. All of the participants in this study were micro, small, and medium-sized businesses in Buleleng District using 99 samples taken use the Slovin. The method a questionnaire was utilized to gather data for this investigation. Which was evaluated on a Likert scale from 1 to 5. This study use a SEM PLS data analysis technique version 4.0